A STUDY OF CHANGES IN PULMONARY FUNCTION WITH ADVANCING AGE AND THE EFFECT OF SMOKING IN MALES OF NORTH KERALA - Shiny George and Biju Baby Joseph (International Journal of Applied Biology and Pharmaceutical Technology, 2013)
As the life expectancy is rising virtually in all proportions throughout the world, awareness of the basic changes in respiratory physiology associated with aging and their clinical implication is important for clinicians. Similarly Chronic obstructive pulmonary disease has emerged as a major health condition worldwide and cigarette smoking has been clearly documented as a risk factor for it. We made an attempt to assess the changes in the pulmonary function with age and also to assess the effect of smoking in males of 18-85 years from North Kerala . The pulmonary function tests were assessed on a computerized spirometer in 247 male subjects, out of which 127 were nonsmokers and 121 were smokers . The results showed a strong negative correlation between various age groups indicating a statistically significant decrease in all pulmonary function parameters as age increases(p<0.01). All the pulmonary function parameters were also significantly decreased in smokers when compared to nonsmokers of the same age groups (p<0.01). The percentage of smokers having airflow limitation (33.1%) was more than 5 times that of the nonsmokers (5.6%). Thus by spirometry airflow limitation can be measured at an early stage so that subsequent morbidity can be minimized by life style changes and more targeted smoking cessation programmes.